Gambaran Kadar Asam Urat, Gula Darah Dan Kolesterol Pada Lansia Di Br. Dinas Kutuh Kelod, Kerambitan, Tabanan - Ni Komang Putri Agustini; Kadek Agus Dwija Putra (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: The world's elderly population reached 13.4% in 2013 and is predicted to increase to 25.3% in 2050. The prevalence of high uric acid levels in the elderly in Indonesia reaches 11.9%, high blood sugar levels reach 35.3. %, and high cholesterol levels as much as 10%. This study aims to determine the level of uric acid, blood sugar and cholesterol in the elderly. Methods: This study used a descriptive analytic design with a cross sectional approach. The research sample used was the elderly aged ? 60 years and over by using the simple random sampling technique in Banjar Dinas Kutuh Kelod, Kerambitan, Tabanan. Data collection was carried out from 7 to 8 June 2020 by means of face-to-face interviews using questionnaire guidelines for respondent characteristics data, and direct examination of uric acid, blood sugar and cholesterol levels using Easy Touch GCU. The data obtained were analyzed using the univariate spss application. Results: Based on univariate analysis, it was found that most of the respondents were 13.2% aged 60 and 69 years, 55.3% were female, 65.8% at the primary education level (SD), and 39.5% worked as farmers. In the bivariate analysis, it was found that most of the respondents or 55.3% had abnormal uric acid levels, 39.5% had abnormal blood sugar levels and 44.7% had abnormal cholesterol levels. Conclusion: Most of the respondents have abnormal uric acid levels while blood sugar and cholesterol are mostly still in the normal category. It is hoped that related parties will continue to carry out screening or early detection, especially in the elderly group, in order to reduce the incidence of non-communicable diseases (PTM) in the elderly.